PROSEDUR KERJA PRAMUSAJI MOLECULE GASTRO BAR DI HOTEL NOVOTEL PEKANBARU - Suci Ananda Bowi; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Hotel Novotel Pekanbaru is one of the best four-star hotels in Pekanbaru with a strategic location. Has a bar called Molecule Gastro Bar which provides excellent beverage service, as evidenced by the small number of guest complaints against Molecule Gastro Bar Novotel Pekanbaru compared to several other hotels. The implementation of these services is carried out by the waiter in accordance with the standards that have been applied. The standard is when before the bar is opened, the bar is opened and the bar is closed. The purpose of this study was to determine the implementation and the obstacles that occurred during the process of the waitress working procedure. This study uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data directly from the field. The key informants of this research are FBM Novotel Pekanbaru, Restaurant Supervisor, Bar Supervisor, Bartender and Waitress. This study uses the technique of collecting observations, interviews and documentation. From the results of this study, it can be seen that the implementation of the bar waiter's work procedures has been running well in accordance with the SOPs that have been determined to be followed so that operations can run well. Keywords: Implementation, SOP, Bar, service, waiter